Effect of surface electrostatic interactions on the stability and folding of formate dehydrogenase from Candida methylica - Ordu, Emel B.; Sessions, Richard B.; Clarke, Anthony R.; Karaguler, Nevin Gul (ELSEVIER SCIENCE BV, 2013)
NAD(+)-dependent formate dehydrogenase (FDH-EC 1.2.1.2) is an important enzyme to regenerate valuable NADH required by NAD(+)-dependent oxidoreductases in enzyme catalysis. The limitation in the thermostability of FDH enzyme is a crucial problem for development of biotechnological and industrial processes, despite of its advantages. In this study, to investigate the contribution of surface electrostatic interaction to the thermostability of FDH from Candida methylica (cmFDH) N187E, H13E, Q105R, N300E, N147R N300E/N147R, N187E/Q105R, N187E/N147R,Y160R, Y302R, Y160E and Y302E mutants were designed using a homology model of cmFDH based on Candida boidinii (cb) by considering electrostatic interactions on the protein surface. The effects of site-specific engineering on the stability of this molecule was analyzed according to minimal model of folding and assembly reaction and deduced equilibrium properties of the native system with respect to its thermal and denaturant sensitivities. It was observed that mutations did not change the unfolding pattern of native cmFDH and increased numbers of electrostatic interactions can cause either stabilizing or destabilizing effect on the thermostability of this protein. The thermodynamic and kinetic results suggested that except relatively improved mutants, three out of the nine single mutations increased the melting temperature of cmFDH enzyme. (c) 2013 Elsevier B.V. All rights reserved,
Keywords: Candida methylica; Electrostatic interaction; Formate dehydrogenase; Protein folding; Enzyme stability; PROTEIN THERMOSTABILITY; STABILIZATION; DENATURATION; BRIDGES; STATE; Biochemistry & Molecular Biology; Chemistry